2014
DOI: 10.1007/s10806-014-9513-z
|View full text |Cite
|
Sign up to set email alerts
|

Same Pig, Different Conclusions: Stakeholders Differ in Qualitative Behaviour Assessment

Abstract: Animal welfare in pig production is frequently a topic of debate and is sensitive in nature. This debate is partly due to differences in values, forms, convictions, interests and knowledge among the stakeholders that constitute differences among their frames of reference with respect to pigs and their welfare. Differences in frames of reference by stakeholder groups are studied widely, but not specifically with respect to animal behaviour or welfare. We explored this phenomenon using a qualitative behaviour as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 32 publications
1
39
0
Order By: Relevance
“…We found similar significant interobserver reliability for FL and FCP groups and significant agreement in GPA dimension 1 and 2 scores between the two observer groups, suggesting that observers in each group scored the body language of the sows in a similar way. Clearly, therefore, selection of either FL or FCP methodology cannot explain discrepancies in conclusions about reliability of observer scores between previous QBA studies Duijvesteijn et al, 2014). Greater understanding of the methodological and statistical procedures will help elucidate the benefits and potential issues associated with using either FL or FCP methods for qualitative behavioural assessment.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We found similar significant interobserver reliability for FL and FCP groups and significant agreement in GPA dimension 1 and 2 scores between the two observer groups, suggesting that observers in each group scored the body language of the sows in a similar way. Clearly, therefore, selection of either FL or FCP methodology cannot explain discrepancies in conclusions about reliability of observer scores between previous QBA studies Duijvesteijn et al, 2014). Greater understanding of the methodological and statistical procedures will help elucidate the benefits and potential issues associated with using either FL or FCP methods for qualitative behavioural assessment.…”
Section: Resultsmentioning
confidence: 99%
“…Wemelsfelder et al (2012) demonstrated consistency and agreement in how pig farmers, veterinarians and animal activists scored pig behaviour, but by contrast, Duijvesteijn et al (2014) reported that pig farmers observed the behaviour of pigs in a more positive way compared to animal scientists and urban citizens. Duijvesteijn et al (2014) used a FL methodology (the same descriptive terms as the present study) while Wemelsfelder et al (2012) used FCP. It is argued that these methodological differences accounted for different outcomes of these two studies (Duijvesteijn et al, 2014).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…For example, Duijvesteijn et al (2014) found that, although observers used terms similarly (largely the same set of descriptive terms were correlated with each of the behavioural dimensions) and had the same intra-observer correlations (each observer saw the same video clip twice), farmers tended to score the behavioural expression of animals more positively than urban citizens or animal scientists. Bokkers et al (2012) compared the scores attributed to the same footage by eight experienced observers for each descriptive term over two viewing sessions, separated by 9 months.…”
Section: 'How Are Observers Selected?'mentioning
confidence: 99%